Faktor yang mempengaruhi pemberian ASI eksklusif - Raj, Jihan Francisca; Fara, Yetty Dwi; Mayasari, Ade Tyas; Abdullah, Abdullah (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
The world’s percentage of Exclusive Breastfeeding (EB) is still low. As in national scope the coverage of infants which was exclusive breastfeeding as much as 68.74 percent in 2018. Data coverage of exclusive breastfeeding in Lampung Province in 2018, is also still below the national exclusive breastfeeding coverage that is 61.63 percent. While the coverage of exclusive breastfeeding in TanggamusDistrict is still lower when compared to the coverage of exclusive breastfeeding in Lampung Province, which only reaches 53.2 percent. Exclusive breastfeeding can be influenced by several factors, including education, cultural customs, and the role of health providers. The purpose of this study was to determine the factors affecting exclusive breastfeeding in Puskesmas Pulau Panggung, Tanggamus District in 2020. This type of research is quantitative, the design of this research is analytic observational using a cross-sectional approach, and the population was mothers who have babies between 7-12 months who visit at Puskesmas Pulau Panggung, with a total sample of 106 respondents. The analysis used univariate and bivariate using the test chi-square. The results obtained by the mother who did not give exclusive breastfeeding as many as 57 people (53.8 percent), the level of maternal education in the low category was 67 people (63.2 percent). Most respondents have good cultural customs, namely 58 people (54.7 percent). Most health providers support exclusive breastfeeding, as many as 65 people (61.3 percent). There is a relationship between the level of education, cultural customs and the role of health providers toward exclusive breastfeeding in Puskesmas Pulau Panggung Tanggamus District, 2020. It is expected that health providers educate mothers about the benefits of exclusive breastfeeding.